To solve questions 10.1 and 10.2 based on the provided geometry and angles related to circles and cyclic quadrilaterals, letβs break down the problem into parts.
Question 10.1
10.1.1 Calculate, with reasons, the numerical values of \(D_1\).
Since \(BD\) is the diameter of the circle, angle \(BMD\) is \(90^\circ\) (angle in a semicircle).
- Given: \(AMC = 128^\circ\).
In triangle \(AMD\):
\[ \text{Angle } D = 180^\circ - AMC - BMD \] \[ D_1 = 180^\circ - 128^\circ - 90^\circ \] \[ D_1 = 180^\circ - 218^\circ = -38^\circ. \]
Since angles cannot be negative, we must reassess \(D_1\).
We are actually calculating angle \(D_1\):
Using the cyclic nature and properties, we also know: \[ D_1 + AMC = 180^\circ \quad (\text{angles opposite in a cyclic quadrilateral}) \] \[ D_1 + 128^\circ = 180^\circ. \] \[ D_1 = 180^\circ - 128^\circ = 52^\circ. \]
Thus: \[ \boxed{D_1 = 52^\circ}. \]
10.1.2 Calculate, with reasons, the numerical values of \(A_1\).
Using the same cyclic quadrilateral properties:
\[ A_1 + B_1 = 180^\circ, \] but we know:
\[ B_1 = D_1 = 52^\circ \quad (\text{as per previous calculation}). \]
Now we have to calculate \(A_1\): \[ A_1 = 180^\circ - B_1. \] Next, we observe angle \(B\): \[ A_1 = 180^\circ - 52^\circ = 128^\circ. \]
Thus: \[ \boxed{A_1 = 128^\circ}. \]
Question 10.2
Using the properties of cyclic quadrilaterals and tangents:
10.2.1 Express \(B_1\) in terms of \(x\) and \(y\).
Since \(E\) is a point where the tangent meets the extended line \(AC\):
By the tangent-secant theorem: \[ B_1 = y \quad \text{(angle between tangent and chord)}. \]
Hence, \[ \boxed{B_1 = y}. \]
10.2.2 Express \(B_2\) in terms of \(x\) and \(y\).
By the same rationale applied in \(B_2\):
- This angle is subtended by arc \(A\) opposite to it on the opposite side: \[ B_2 = x \quad \text{(from angle subtending opposite)}. \]
Thus: \[ \boxed{B_2 = x}. \]
10.2.3 Express \(D_1\) in terms of \(x\) and \(y\).
In the case of \(D_1\), we apply the property of angles in opposite arcs: \[ D_1 + y + x = 180^\circ, \] therefore:
\[ D_1 = 180^\circ - (x + y). \]
Thus, \[ \boxed{D_1 = 180^\circ - x - y}. \]
Summary of Results:
- \(D_1 = 52^\circ\)
- \(A_1 = 128^\circ\)
- \(B_1 = y\)
- \(B_2 = x\)
- \(D_1 = 180^\circ - x - y\)